Polymerization and modeling of phenolic resins from crude wood resin in the presence of AlCl3 - Ömür Aras; Murat Ertaş; Muhammed Yusuf Aksakal; Naile Angın; Merve Genç (Turkish Journal of Forestry)
With increasing environmental problems, interest in natural polymers that have less toxic effects on the environment and are biodegradable is increasing day by day. Natural resin is a promising and valuable renewable non-wood forest product and is used as a natural resource in the production of many biochemical products. In this study, it is aimed to synthesize terpene-rosin phenolic resin (TRFR) from crude wood resin, turpentine and phenol in the presence of AlCl3 with an innovative polymerization technique. Before proceeding to the synthesis stage, the raw resin was separated into turpentine and rosin by distillation and characterized with a gas chromatography - mass spectroscopy (GC-MS) device. The synthesized TRFR samples were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance Spectroscopy (NMR), acid number, saponification number and softening point analyses. Moreover, the modeling of synthesis reactions Artificial Neural Network (ANN) was designed with 2 inputs (temperature and turpentine/crude wood resin ratio) and 4 outputs (reaction yield, acid value, saponification value and softening point). The highest reaction efficiency was found in the sample produced at 60°C with a turpentine/crude wood resin ratio of 1/2. The lowest acidity and saponification values were calculated as 90.79 and 103.79 mg KOH/g, respectively. The highest softening point was found to be 79°C.